Comparison of antimicrobial activity of crude ethanolic extracts of five different plants against acne-inducing bacteria - Aminuddin, Aiza Izyani (Universiti Sains Malaysia, 2015)
Acne vulgaris is defined as a typical skin disorder among adolescence, causing inflammation of pilosebaceous follicle which is characterized by comedones, papules, pustules, cysts, nodules and often scars in face, neck, upper trunk and also arms. Propionibacterium acnes and Staphylococcus epidermidis have been recognized as a causal factor in acne formation. This study was conducted to compare the antimicrobial activity of five plant extracts of Piper belle, Aloe vera, Solanum lycopersicum, Cinnamomum zeylanicum and Cucumis sativus against P. acnes and 5. epidermidis. The antimicrobial activity of five ethanolic plant extracts were investigated against the two acne-inducing bacteria using well diffusion and minimum inhibitory concentration (MIC) method. The well diffusion method result revealed that the ethanolic extracts of Piper betle, Aloe vera, Solanum lycopersicum, Cinnamomum zeylanicum and Cucumis sativus showed mean of inhibition zone diameter of 29.0 mm, 7.7 mm, 10.7 mm, 13.9 mm and 11.5 mm respectively against P. acnes bacteria and mean of inhibition zone diameter of 32.0 mm, 30.7 mm, 13.0 mm, 14.3 mm and 15.3 mm respectively against S. epidermidis bacteria. The mean value of MIC against P. acnes for Piper betle extract and Cinnamomum zeylanicum extract showed 39.06 mg/ml and 2.45 mg/ml respectively. Whereas the mean value of MIC of all five ethanolic extracts of Piper betle and Aloe vera, showed 2.45 mg/ml dan 78.13 mg/ml respectively. Meanwhile, the other ethanolic extracts of Solanum lycopersicum, Cinnamomum zeylanicum and Cucumis sativus against S. epidermidis bacteria showed 39.06 mg/ml. This suggests that Piper betle and Cinnamomum zeylanicum extracts have showed the most effective antimicrobial effects against acne-inducing bacteria. However, all of the ethanolic extracts were found to have potency against acne-inducing bacteria which can be further evaluated in animal and clinical research that can be used as an alternative treatment of acne commercially.